Prolegomena to a critical theory of the global order. Issue 3 (29th November 2019) - Held, David; Maffettone, Pietro
ABSTRACT: We start from, and expand on, a basic insight in negative dialectic, namely, that our main concern should be with the absolute worst in political life. We then consider how this might have an impact on the way we understand the role and grounds of moral equality. Subsequently, we move on to explain the importance of decency in political morality. Finally, we take a closer look to basic data about global poverty and inequality and what these might tell us in light of our analysis of the foundations of moral equality and its relationship to social cruelty.